Zonal differences in risk and pattern of pedicle screw perforations in adolescent idiopathic scoliosis (AIS): a computerized tomography (CT) review of 1986 screws - Chan, Chris Yin Wei; Kwan, Mun Keong (Springer Verlag, 2018)
Purpose: To evaluate the zonal differences in risk and pattern of pedicle screw perforations in adolescent idiopathic scoliosis (AIS) patients. Methods: The scoliosis curves were divided into eight zones. CT scans were used to assess perforations: Grade 0, Grade 1(< 2 mm), Grade 2(2–4 mm) and Grade 3(> 4 mm). Anterior perforations were classified into Grade 0, Grade 1(< 4 mm), Grade 2(4–6 mm) and Grade 3(> 6 mm). Grade 2 and 3 (except lateral grade 2 and 3 perforation over thoracic vertebrae) were considered as ‘critical perforations’. Results: 1986 screws in 137 patients were analyzed. The overall perforation rate was 8.4% after exclusion of the lateral perforation. The highest medial perforation rate was at the transitional proximal thoracic (PT)/main thoracic (MT) zone (6.9%), followed by concave lumbar (6.7%) and convex main thoracic (MT) zone (6.1%). The overall critical medial perforation rate was 0.9%. 33.3% occurred at convex MT and 22.2% occurred at transitional PT/MT zone. There were 39 anterior perforations (overall perforation rate of 2.0%). 43.6% occurred at transitional PT/MT zone, whereas 23.1% occurred at concave PT zone. The overall critical anterior perforation rate was 0.6%. 5/12 (41.7%) critical perforations occurred at concave PT zone, whereas four perforations occurred at the transitional PT/MT zone. There were only two symptomatic left medial grade 2 perforations (0.1%) resulting radiculopathy, occurring at the transitional main thoracic (MT)/Lumbar (L) zone. Conclusion: Overall pedicle perforation rate was 8.4%. Highest rate of critical medial perforation was at the convex MT zone and the transitional PT/MT zone, whereas highest rate of critical anterior perforation was at the concave PT zone and the transitional PT/MT zone. The rate of symptomatic perforations was 0.1%.